Role of Rural Women in Community Radio with special reference to APNA RADIO and GURGAON KI AWAAZ - Neha Singh; Saumya Gupta (Dev Sanskriti: Interdisciplinary International Journal)
In rural areas, there is a greater need for resources to empower women compared to urban areas. As we all know, the government has launched many schemes for rural development as well as for women’s development. Despite this, encouraging and empowering women in rural areas remains a significant challenge. When someone says we are living in the 21st century, the first question that comes to mind is, "Are we really living in the 21st century?" Women in rural areas are still primarily occupied with household chores.